ANALISIS EFEKTIVITAS ELECTRONIC TRAFFIC LAW ENFORCEMENT (ETLE) DALAM SISTEM PENEGAKAN HUKUM DI KABUPATEN TANGERANG - Tiessa, Amelia Noviana; Lesmana, Sri Jaya; Indayatun, Ratna (SOSCIED, 2025)
The problem of undiscipline and disobedience in driving traffic is a problem that is still faced by law enforcement officials in Indonesia. The birth of Electronic Traffic Law Enforcement (ETLE) is a complementary effort in overcoming the problem of traffic order violations. So that its position does not eliminate conventional methods in direct traffic control. This study aims to analyze the effectiveness of ETLE in the law enforcement system in Tangerang Regency. The method used is empirical legal research using primary data and secondary data. The results show that although the ETLE system can improve efficiency and accuracy in traffic law enforcement, its effectiveness is still constrained by several factors. The limited number of monitoring points, lack of socialization to the public, and low legal awareness of motorists are the main obstacles. Although the number of traffic violations netted through ETLE is quite significant, there is still a need for infrastructure improvement, better socialization, and an approach to form a stronger legal culture among the community so that traffic law enforcement can run optimally and sustainably.